If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -6 = 2x + -24 Reorder the terms: -6 + X = 2x + -24 Reorder the terms: -6 + X = -24 + 2x Solving -6 + X = -24 + 2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + X = -24 + 6 + 2x Combine like terms: -6 + 6 = 0 0 + X = -24 + 6 + 2x X = -24 + 6 + 2x Combine like terms: -24 + 6 = -18 X = -18 + 2x Simplifying X = -18 + 2x
| u(6u+5)=1 | | 6=-15x | | (3/5-3/10)*30 | | 76=-4m | | h=-16t^2+56t+40 | | x^3/2=14 | | 2(3.14)(12)= | | 0.125x=-3 | | b/2+5=-7 | | Y/3=15 | | 8c=-122 | | 2(z-x)=5x-(3x+2) | | 25/57=849/5x | | w^8+11w^4+10= | | 7x+5y=9 | | y=2/5-2 | | 8b+11-3b=2b-3+5 | | 3/4x-7=17 | | 4x^2+17=5 | | (45-27)n= | | x+1/3+x+2/7=2 | | 14-3(5t-12)=1-(29t+1) | | 3x-(2x-7)=3(1+x) | | S=r | | x^2+2xy+y^2=x^2+y^2 | | 3a+6-2a+9+5a= | | 9k+3=8k+19 | | x^2+2xy+y^2=x+y^2 | | 1/6(2x-9)=7 | | 7-2i= | | 31=-42+x | | f(x)=3x+7 |